The pathology and pathobiology of bicuspid aortic valve: State of the art and novel research perspectives1. (24th June 2015) - Mathieu, Patrick; Bossé, Yohan; Huggins, Gordon S; Della Corte, Alessandro; Pibarot, Philippe; Michelena, Hector I.; Limongelli, Giuseppe; Boulanger, Marie‐Chloé; Evangelista, Arturo; Bédard, Elisabeth; Citro, Rodolfo; Body, Simon C; et al.
Abstract: Bicuspid aortic valve is the most prevalent cardiac valvular malformation. It is associated with a high rate of long‐term morbidity including development of calcific aortic valve disease, aortic regurgitation and concomitant thoracic aortic aneurysm and dissection. Recently, basic and translational studies have identified some key processes involved in the development of bicuspid aortic valve and its morbidity. The development of aortic valve disease and thoracic aortic aneurysm and dissection is the result of complex interactions between genotypes, environmental risk factors and specific haemodynamic conditions created by bicuspid aortic valve anatomy. Herein, we review the pathobiology of bicuspid aortic valve with a special emphasis on translational aspects of these basic findings. Important but unresolved problems in the pathology of bicuspid aortic valve and thoracic aortic aneurysm and dissection are discussed, along with the molecular processes involved.